1954
DOI: 10.1099/00221287-10-2-221
|View full text |Cite
|
Sign up to set email alerts
|

Gene Interactions: the Mode of Action of the Suppressor of Acetate-requiring Mutants of Neurospora crassa

Abstract: SUMMARY : Certain single-gene acetate-requiring mutants of Neurospora crassa (ac) are deficient in their ability to oxidize pyruvate directly, but can decarboxylate pyruvate to acetaldehyde and can form ethanol. The growth characteristics of the nc mutants indicate that they can form acetate from glucose or ethanol. ac Mutants are inhibited by glucose or sucrose. This glucose inhibition is relieved by the singlegene suppressor mutations sp and car which lower the activity of pyruvic carboxylase, decrease the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1955
1955
1967
1967

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Examples of suppression by both the above mechanisms are known. [2][3][4] In addition it has been suggested that certain suppressor genes might act by permitting the formation of new, effective enzymes to function for the absent or defective ones. In Neurospora crassa several cases of suppression are known in mutants which form an altered protein immunologically related to the enzyme tryptophan synthetase;' in the presence of the suppressor gene normal enzymatic activity appears.…”
mentioning
confidence: 99%
“…Examples of suppression by both the above mechanisms are known. [2][3][4] In addition it has been suggested that certain suppressor genes might act by permitting the formation of new, effective enzymes to function for the absent or defective ones. In Neurospora crassa several cases of suppression are known in mutants which form an altered protein immunologically related to the enzyme tryptophan synthetase;' in the presence of the suppressor gene normal enzymatic activity appears.…”
mentioning
confidence: 99%
“…We therefore investigated the characteristics of this type of suppressor to determine whether a new type of gene interaction was represented. Our results indicate that in methionine biosynthesis, these particular suppressors act by preventing the formation of an inhibitor accumulated as a result of the original mutation to auxotrophy, an action similar in nature to that of the suppressors of the acetate-requiring mutants (Strauss & Pierog, 1954). In the course of our studies, some observations were and M7 respond to either cystathionine, homocysteine or methionine, but not to cysteine, these strains are not alleles.…”
Section: Introductionmentioning
confidence: 51%
“…Such an action by the s u gene might account for the restoration of cystathionase I and I1 activities observed in m e mutants by Fischer (1957). This scheme is analogous to that devised to account for the behaviour of the suppressors of the acetate-requiring mutants of Neurospora (Strauss & Pierog, 1954). It was supposed a t that time that the acetate suppressors lowered the production of an inhibitor (acetaldehyde) formed in excess as a result of the first mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvic acid, AMC and C, condensation products which do not require complete oxidation accumulate in cultures of the SUC mutants (necessarily grown in the presence of nitrogen salts) because of the deficiency in the dicarboxylic acid catalyst required for C, fragment oxidation. The same accumulation products are produced in the suc mutants, where there is no immediate block to pyruvate oxidation as in the ac mutants (Strauss & Pierog, 1954), where there is a block in the oxidation of pyruvate : another illustration of the danger of using accumulations as evidence of genetic block (Adelberg, 1953). The relationship between succinate, a growth requirement, and AMC, a by-product of a true intermediate, is another case in which an end product controls the accumulation of a precursor (Strauss, 1955a, b ;Adelberg & Umbarger, 1953).…”
Section: Cl?mentioning
confidence: 99%
“…-f See (Strauss & Pierog, 1954). The at locus apparently acts only as a modifier to the SUC gene, preventing response of SUC strains to acetate.…”
Section: B S Straussmentioning
confidence: 99%